Hopf and zero-Hopf bifurcations in the Hindmarsh–Rose system - Buzzi, Claudio [UNESP] (2016)
We prove the existence of the classical Hopf bifurcation and of the zero-Hopf bifurcation in the Hindmarsh–Rose system. For doing this, some adequate change in parameters must be done in order that the computations become easier.